Land Acquisition for National Strategic Projects to Enhance the Interconnectedness and Supply Chain Infrastructure - Andriani Latania Triramdhani; Nia Kurniati; Nyulistiowati Suryanti; Supraba Sekarwati (International Journal of Supply Chain Management, 2020)
Abstract- Infrastructure development in Indonesia has a very significant influence on national economic growth and supply chain interconnectedness. The current regime truly pays more attention to infrastructure development by rapidly developing supply chain infrastructure. It became the main program in his regime. To realize and launch the supply chain infrastructure and development, it certainly requires land acquisition. As a form of government attention to supply chain infrastructure development, various policies are made by the government. However, the legal norms in the policy carry the risk of antinomy of norms for the land acquisition process in supply chain infrastructure development. The study aims to investigate the need of land acquisition concept for a national strategic project to improve people's welfare to increase the national economic growth by emphasizing on supply chain infrastructure and connectivity development programs. This study used qualitative research methods with a normative and casuistic approach. The results showed that the concept of accelerating land acquisition for national strategic projects can reach an equilibrium point, both for the welfare of the people as land owners and economic growth targeted as an objective of improving people's connectiveness, supply chain competitiveness and economic productivity.